Protective evaluation of the commercialized porcine reproductive and respiratory syndrome virus vaccines in piglets challenged by NADC34-like strain - Liu, Zhicheng; Li, Chaosi; Hu, Yulong; Fang, Shuhe; Li, Xiangdong; Zhang, Chunhong; Huang, Lv; Qian, Jie; Wang, Gang; Fan, Aihua; Zhang, Jianfeng; Geri, Letu (Frontiers in Microbiology, 2024)
In China, the porcine reproductive and respiratory syndrome virus (PRRSV) has undergone several variations over the decades and contributed to the diversity of the clinical epidemic PRRSV strains. This has complicated the prevention and control of PRRS. In particular, the efficacy of the currently available commercial vaccines against the highly pathogenic NADC34-like strains is unclear. Therefore, the objective of this study was to evaluate the protection efficacy of three commercial PRRS modified-live virus (MLV) vaccines derived from classical PRRS VR2332 MLV and R98 MLV against challenge with a heterologous NADC34-like PRRSV strain, JS2021NADC34, which has high pathogenicity in pigs. PRRSV-and antibody-free piglets were immunized with the PRRS VR2332 MLV vaccine or either of two R98 MLV vaccines (from different manufacturers) and were challenged with the JS2021NADC34 strain 28 days after immunization. Rectal temperature, clinical symptoms, viremia and viral shedding from the nose, gross lesions in the thymus and lungs, microscopic lesions and viral distribution in the lungs, as well as the humoral immune response and mortality rates were recorded over a 14-day post-challenge period. The results showed that PRRS VR2332 MLV had better efficacy against the JS2021NADC34 challenge than PRRS R98 MLV, with vaccinated piglets in the former group showing transient and mild symptoms, mild pathological lesions in the lungs, mild thymic atrophy, and low viral levels in sera and nasal swabs, as well as better growth performance and a 100% survival rate.In contrast, two PRRS R98 MLVs exhibited limited efficacy against the JS2021NADC34 challenge, with the piglets in two R98 groups showing obvious clinical symptoms and pathological changes in the lungs and thymus; moreover, there were two deaths caused by PRRS in two R98 groups, respectively. Despite this, the mortality rate was lower than that of the unvaccinated piglets that were challenged with JS2021NADC34. The cumulative results demonstrate that PRRS VR2332 MLV was partly effective against the highly pathogenic PRRSV NADC34-like strain based on the observations over the 14-day post-challenge period.Thus, it might be a viable option among the commercially available vaccines for control of NADC34-like virus infections in swine herds.